Cardiac repolarisation indices are associated with oxygen consumption during maximal exercise test in highly-trained cross-country skiers - Veselik, A. K.; Arteyeva, N. V.; Varlamova, N. G.; Loginova, T. P.; Garnov, I. O.; Bojko, E. R.; Azarov, J. E. (Journal of Sports Sciences, 2024)
The objective of this study was to test the vectorelectrocardiographic T-wave characteristics for their associations with oxygen consumption (VO2) and physical performance during a maximal cardiopulmonary exercise test (CPET) in highly trained cross-country skiers. Male highly trained cross-country skiers (n = 30) performed the maximal CPET on the bicycle ergospirometric "Oxycon Pro" system with simultaneous oxygen consumption (VO2) and electrocardiogram recording. The measurements were done at rest; the stage preceding anaerobic threshold (preAnT); peak load; and recovery. The anaerobic threshold was estimated by respiratory exchange ratio. Physical performance was estimated by maximal oxygen consumption (VO2max/kg). VECG characteristics were calculated using Kors transformation procedure. During the test, the magnitudes of T-vector, Tx and Ty components decreased until preAnT, then stayed relatively stable until peak load, and reversed during recovery. In univariate linear regression analysis, T-vector amplitude and Tx, Ty and Tz magnitudes were associated with VO2/kg during the test (p < 0.010). The baseline T-vector characteristics were not associated with physical performance. At the preAnT stage, Tx and T-vector amplitude were associated with VO2max/kg (RC 12.70, 95% CI 0.68-24.73, p = 0.039 and RC 10.64, 95% CI 1.62-19.67, p = 0.023, respectively).